2019
DOI: 10.1001/jamanetworkopen.2019.2561
|View full text |Cite
|
Sign up to set email alerts
|

Association of Peritumoral Radiomics With Tumor Biology and Pathologic Response to Preoperative Targeted Therapy forHER2 (ERBB2)–Positive Breast Cancer

Abstract: Key Points Question Can quantitative imaging features extracted from the tumor and tumor environment on breast magnetic resonance imaging characterize tumor biological features relevant to outcome of targeted therapy? Findings In this diagnostic study of 209 patients, among HER2 ( ERBB2 )-positive breast cancers, an intratumoral and peritumoral imaging signature capable of discriminating the response-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
203
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 223 publications
(234 citation statements)
references
References 79 publications
(164 reference statements)
17
203
0
2
Order By: Relevance
“…There is emerging evidence that predictive models should not be limited to mere tumor areas. Recent studies 24 , 25 , 26 , 37 , 38 , 39 , 40 have shown that the surrounding regions may provide complementary information on tumor heterogeneity in other cancers. Here we proposed a noninvasive, CT-based radiomics model with favorable predictive value using both intratumoral and peritumoral radiomics features to predict the possibility of pCR in patients with ESCC before receiving nCRT.…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence that predictive models should not be limited to mere tumor areas. Recent studies 24 , 25 , 26 , 37 , 38 , 39 , 40 have shown that the surrounding regions may provide complementary information on tumor heterogeneity in other cancers. Here we proposed a noninvasive, CT-based radiomics model with favorable predictive value using both intratumoral and peritumoral radiomics features to predict the possibility of pCR in patients with ESCC before receiving nCRT.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomic feature selection was implemented via a two-stage process, with methodological choices based on previous large-scale comparisons of feature selection schemes [54,55]. First, a combination of significance testing and correlation testing was implemented [54] to individually prune F T and F S in order to remove potentially redundant features (whose correlation coefficient was >0.6 [56]). The resulting pruned feature sets were denoted F T and F S for texture and shape features, respectively.…”
Section: Identifying Relevant Radiomic Features Associated With Pathomentioning
confidence: 99%
“…These novel techniques can determine immune responses such as macrophage activation and lymphocyte infiltration, which has particular relevance in IO, where different lesions can have different TMEs resulting in heterogeneous response patterns. These radiomic signatures have shown promise in multiple tumour types, demonstrating both prognostic and predictive features 152–155 . Leiserson et al developed a multifactorial model for response to ICIs, utilizing an ML method that automatically selects informative features from imported data, and incorporates clinical, tumour, and immunologic features into its model to simultaneously predict clinical benefit 156 .…”
Section: Novel Ici Approaches To Precision Oncologymentioning
confidence: 99%